Assembly of ceria-Nrf2 nanoparticles as macrophage-targeting ROS scavengers protects against myocardial infarction - Liao, Wenjing; Lin, Jinduan; Wang, Wenli; Zhang, Ming; Chen, Yanfang; Li, Xin; Liu, Huan; Wang, Pan Xia; Zhao, Guojun; Fu, Jijun; Wu, Xiaoqian (Frontiers in Pharmacology, 2025)
Myocardial infarction (MI) is a leading cause of morbidity and mortality worldwide, and mitigating oxidative stress is crucial in managing MI. Nuclear factor erythroid 2-related factor 2 (Nrf2) plays a critical role in combating oxidative stress and facilitating cardiac remodeling post-MI. Here, we engineered Cerium oxide (CeO2) nanoparticle-guided assemblies of ceria/Nrf2 nanocomposites to deliver Nrf2 plasmids. The CeO2/Nrf2 nanocomposites effectively activated the Nrf2/antioxidant response element (ARE) signaling pathway both in vivo and in vitro. In a mouse MI model induced by permanent ligation of the left anterior descending artery (LAD), CeO2/Nrf2 nanocomposites were administered via tail vein injection, predominantly targeting circulating monocytes and macrophages which will be recruited to the heart post MI due to the acute inflammatory response. We demonstrated that CeO2/Nrf2 nanocomposites alleviated cardiac systolic dysfunction and significantly reduced infarct size and scar fibrosis post-MI. Furthermore, CeO2/Nrf2 nanocomposites effectively mitigated MI-induced oxidative stress and downregulated Nrf2-regulated inflammatory genes (tumor necrosis factor-α, IL-6, and inducible nitric oxide synthase), thereby reducing cardiomyocyte apoptosis. These findings indicate that CeO2/Nrf2 nanocomposites significantly enhance Nrf2 signaling activation and confer protection against MI. This study identifies CeO2/Nrf2 nanocomposites as a promising strategy for post-MI therapy.